2011
DOI: 10.1017/s0266462310001315
|View full text |Cite
|
Sign up to set email alerts
|

Introducing patients' and the public's perspectives to health technology assessment: A systematic review of international experiences

Abstract: There are few published examples of experiences involving patients and the public in HTA. These examples show that patients' or the public's perspectives could add important dimensions to the evaluation of health technologies. However, there is a need to develop more systematic approaches to considering patients' and the public's perspectives in HTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
181
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(191 citation statements)
references
References 37 publications
3
181
0
7
Order By: Relevance
“…Their study suggests that researchers are adapting 'jury' methods to attempt to meet the needs of policymakers, but because of tension between research aims and deliberative ideals, their success has been limited. Looking beyond the use of citizens' juries, other reviews show that public participation in deliberative events is an increasingly prominent feature of research in healthcare priority setting (Mitton et al, 2009), and, to a lesser extent, health technology assessment [HTA] (Gagnon et al, 2011). Mitton (2009) andGagnon's (2011) groups found that although the public's perspective added an important dimension to policy work, and governments appear to recognize the benefits of consulting multiple publics there is often poor alignment between deliberative research outcomes and actual policies.…”
Section: Figure 1 Types Of Deliberative Forummentioning
confidence: 99%
See 1 more Smart Citation
“…Their study suggests that researchers are adapting 'jury' methods to attempt to meet the needs of policymakers, but because of tension between research aims and deliberative ideals, their success has been limited. Looking beyond the use of citizens' juries, other reviews show that public participation in deliberative events is an increasingly prominent feature of research in healthcare priority setting (Mitton et al, 2009), and, to a lesser extent, health technology assessment [HTA] (Gagnon et al, 2011). Mitton (2009) andGagnon's (2011) groups found that although the public's perspective added an important dimension to policy work, and governments appear to recognize the benefits of consulting multiple publics there is often poor alignment between deliberative research outcomes and actual policies.…”
Section: Figure 1 Types Of Deliberative Forummentioning
confidence: 99%
“…Mitton and colleagues (2009) surveyed the intention and methods of public engagement exercises in health priority setting. And Gagnon's (2011) group focused on the extent of patient and public involvement in health technology assessment. We complement and extend this work by answering the following questions:…”
Section: Figure 1 Types Of Deliberative Forummentioning
confidence: 99%
“…Citizens can also help articulate the overarching values to guide assessments. HTA agencies have begun to explore a range of methods for engaging various publics in their activities [39][40][41]. Although these experiences have yielded promising insights, much developmental work remains to be done to specify which publics to involve in what activities and when along the stages of HTPA processes.…”
Section: From Evidence To Intelligencementioning
confidence: 99%
“…In the long run, the transparency of patient and public involvement [84][85][86] might be enhanced by creating a register of individuals and organisations interested in contributing regularly to drug evaluation and willing to publically disclose their conflicts of interest [87]. The register could then become the basis for selecting members of a permanent advisory body, funded by the AHTAPol, comprising a range of condition areas, general patient associations, and members of the public.…”
Section: Institutionalisation Of Patient and Public Involvementmentioning
confidence: 99%